2020
DOI: 10.3390/nu12082187
|View full text |Cite
|
Sign up to set email alerts
|

The Role of District Wellness Policies in Encouraging Student Participation in the School Breakfast Program, United States

Abstract: Eating breakfast is associated with better academic performance and nutrition and lower risk of obesity, but skipping breakfast is common among children and adolescents, and participation in the U.S. Department of Agriculture’s School Breakfast Program (SBP) is low. This study assessed the association between school district wellness policy provisions coded as part of the National Wellness Policy Study and student SBP participation and acceptance of the breakfasts provided using cross-sectional survey data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…Researchers have found that almost all US school districts have complied with this legislation and have created written wellness policies ( 9 ). Evaluations of strength and comprehensiveness indicate that policies have improved over time; however, there is still considerable variability across districts ( 10 ).…”
Section: History Of Wellness-related School Policies In the United St...mentioning
confidence: 99%
“…Researchers have found that almost all US school districts have complied with this legislation and have created written wellness policies ( 9 ). Evaluations of strength and comprehensiveness indicate that policies have improved over time; however, there is still considerable variability across districts ( 10 ).…”
Section: History Of Wellness-related School Policies In the United St...mentioning
confidence: 99%
“…Children spend an average of 6.5 h in school per day [ 14 , 15 ], eat two meals per day at school [ 16 ], and, on average, receive up to 40% of their physical activity during school hours [ 17 ]. Comprehensive and well-implemented LWPs are consistently associated with superior school district health environments as well as nutritional and physical activity outcomes [ 18 , 19 , 20 , 21 ]. Thus, LWPs could play substantial roles in reducing childhood obesity [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It leads to the improvement of healthy habits throughout life, (13). Skipping breakfast is especially common among older children, adolescents, and females, because eating breakfast is associated with good nutrition, better academic performance, and a lower risk of obesity (14), and that skipping breakfast and eating snacks has an impact on academic performance among adolescents (15), and that the consumption of breakfast is positively affected by family factors such as the type of family, the education of the mother and father, the occupation of the mother and father and the monthly income of the family (16).…”
Section: Introductionmentioning
confidence: 99%